Neuroprotective Effects of Methyl Caffeate against Hydrogen Peroxide-Induced Cell Damage: Involvement of Caspase 3 and Cathepsin D Inhibition - Danuta Jantas; Jakub Chwastek; Janusz Malarz; Anna Stojakowska; Władysław Lasoń (Biomolecules, 2020)
Finding effective neuroprotective strategies to combat various neurodegenerative disorders still remain a clinically unmet need. Methyl caffeate (MC), a naturally occurring ester of caffeic acid, possesses antioxidant and anti-inflammatory activities; however, its role in neuroprotection is less investigated. In order to better characterize neuroprotective properties of MC, we tested its effectiveness in various models of neuronal cell injury in human neuroblastoma SH-SY5Y cells and in mouse primary neuronal cell cultures. MC at micromolar concentrations attenuated neuronal cell damage induced by hydrogen peroxide (H2O2) in undifferentiated and neuronal differentiated SH-SY5Y cells as well as in primary cortical neurons. This effect was associated with inhibition of both caspase-3 and cathepsin D but without involvement of the PI3-K/Akt pathway. MC was neuroprotective when given before and during but not after the induction of cell damage by H2O2. Moreover, MC was protective against 6-OHDA-evoked neurotoxicity in neuronal differentiated SH-SY5Y cells via inhibition of necrotic and apoptotic processes. On the other hand, MC was ineffective in models of excitotoxicity (induced by glutamate or oxygen–glucose deprivation) and even moderately augmented cytotoxic effects of the classical apoptotic inducer, staurosporine. Finally, in undifferentiated neuroblastoma cells MC at higher concentrations (above 50 microM) induced cell death and when combined with the chemotherapeutic agent, doxorubicin, it increased the cell damaging effects of the latter compound. Thus, neuroprotective properties of MC appear to be limited to certain models of neurotoxicity and depend on its concentrations and time of administration.